Host-directed therapy against mycobacterium tuberculosis infections with diabetes mellitus - Zhao, Li; Fan, Ke; Sun, Xuezhi; Li, Wei; Qin, Fenfen; Shi, Liwen; Gao, Feng; Zheng, Chunlan (Frontiers in Immunology, 2024)
Tuberculosis (TB) is caused by the bacterial pathogen Mycobacterium tuberculosis (MTB) and is one of the principal reasons for mortality and morbidity worldwide.Currently, recommended anti-tuberculosis drugs include isoniazid, rifampicin, ethambutol, and pyrazinamide. TB treatment is lengthy and inflicted with severe sideeffects, including reduced patient compliance with treatment and promotion of drugresistant strains. TB is also prone to other concomitant diseases such as diabetes and HIV. These drug-resistant and complex co-morbid characteristics increase the complexity of treating MTB. Host-directed therapy (HDT), which effectively eliminates MTB and minimizes inflammatory tissue damage, primarily by targeting the immune system, is currently an attractive complementary approach. The drugs used for HDT are repositioned drugs in actual clinical practice with relative safety and efficacy assurance. HDT is a potentially effective therapeutic intervention for the treatment of MTB and diabetic MTB, and can compensate for the shortcomings of current TB therapies, including the reduction of drug resistance and modulation of immune response. Here, we summarize the state-of-the-art roles and mechanisms of HDT in immune modulation and treatment of MTB, with a special focus on the role of HDT in diabetic MTB, to emphasize the potential of HDT in controlling MTB infection.